Effectiveness of Learning Management System (LMS) in Improving Student Learning Independence - Chen, Nathan; Razak , Omar (International Journal of Educational Insights and Innovations, 2024)
The rapid advancement of educational technology has significantly transformed learning methodologies, with Learning Management Systems (LMS) playing a crucial role in facilitating self-directed learning. This study aims to evaluate the effectiveness of LMS in enhancing students' learning independence by examining its impact on motivation, time management, and critical thinking skills. Using a mixed-method approach, data was collected from students utilizing LMS platforms through surveys, interviews, and performance assessments. The findings indicate that LMS positively influences students' ability to learn independently by providing structured content, interactive resources, and self-assessment tools. Moreover, the flexibility of LMS allows students to learn at their own pace, fostering a sense of responsibility and autonomy. However, challenges such as digital literacy and motivation gaps remain significant barriers. The study concludes that while LMS contributes to improving learning independence, its effectiveness depends on user engagement and institutional support. Recommendations for optimizing LMS implementation include personalized learning paths, gamification, and enhanced teacher-student interaction.